Humor dalam Buku Komik ‘Lawak Kampus’: Analisis Teori Grice (LITPAM, 2024)
This research aims to find out the hidden meanings found in the comic book 'Lawak Kampus' by Keith. The research questions are, (1) What maxims exist in the ‘Lawak Kampus’ comic? and (2) Does the comic 'Lawak Kampus' have maximum compliance with the principle of cooperation or vice versa? The objectives of this study are (1) To identify the implied meaning behind the four-part comic 'Lawak Kampus', (2) To analyze the maxims of the principle of cooperation found in the comic 'Lawak Kampus' and (3) To classify the maxims of the principle of cooperation as categorized in Grice's theory (1975). This study uses a qualitative method which is a descriptive type. In producing this study, three methods were used, namely the library method, the data collection method and the data analysis method. The data taken is from a comic book 'Lawak Kampus Kompilasi Mantap 3' Malay version. The selection of data is random by selecting 20 data from the comic book that has humor for each story. This study only focuses on the humor in the comic book. Next, the results of the 20 data that have been selected will be analyzed one by one by explaining the implicature used in each title whether there is compliance or violation of the maximum principle of cooperation in the comic or vice versa. As a result of the study, there are four maxims of the principle of cooperation in the comic book. In addition, this study uses the theory from Grice (1975). Therefore, this study looks in terms of the hidden meanings found in the comic.